Psychology and the problematic of “the African” - Kiguwa, Peace; Segalo, Puleng (PINS-Psychology in Society, 2018)
In this commentary we extend Manganyi’s critique of Eurocentric and Western scientific practice of engaging the African Other as inherently strange and unfamiliar. This particular mode of representation and knowing the Other is functional in embodying a uniqueness that renders African bodies as non-human. It is also functional in reifying a science that pretends to objective practice. We take up Manganyi’s notion of making strange to interrogate some of the nuances of what it means to engage the Other in the context of a socio-political and historical analysis. We further present some of the problematics of trying to understand the current contexts of social ills in society through a lens that does not reproduce this dehumanising meaning of subjectivities and groups, and that does not end up making strange what we are trying to understand. Lastly, we posit some problematics concerning how Africans as colonised peoples have been made strange to themselves and become entangled in relations of violence and power that make the familiar unfamiliar even to themselves.